Flexural behavior of BMSC beam exposed to the harsh environment - Xiangchao Zeng; Haiyan Ma; Hongfa Yu; Peng Yue (Results in Engineering, 2023)
Basic magnesium sulfate cement concrete (BMSC) was invented in 2013, which has many merits: excellent mechanical performance, good toughness and good crack resistance. But the mechanical performance of BMSC beams laid in the harsh weather for a long time is not known. The mechanical properties of six corroded reinforced BMSC beams were studied for applying this new concrete to practical engineering. It can be found that there is no rust crack before loading test. The bearing capacity of corroded reinforced BMSC beam laid in the harsh environment for two years, especially in the weather of long-term freeze-thaw cycles and acid rain, degraded by 11.9 % and the bending rigidity degraded by 17.0 %. Based on the attenuation of steel corrosion and deterioration of BMSC after the harsh exposure, the model of bearing capacity and cracking load of the corrosion-damaged BMSC beam is proposed. This paper is helpful to the application of BMSC members in the area of harsh environments.